A meta-analysis of the effects of synchronization protocols applied to sheep in Turkey on pregnancy rates during breeding and non-breeding seasons - Arikan, Mehmet Saltuk; Mat, Burak; Alkan, Hasan; Cevrimli, Mustafa Bahadir; Akin, Ahmet Cumhur; Sahin, Tugba Sarihan; Tekindal, Mustafa Agah (Wiley, 2021)
This study aimed to determine common pregnancy rates and effect sizes with meta-analysis of studies investigating the effect of different synchronization protocols applied to sheep during breeding and non-breeding seasons on pregnancy rates. Common pregnancy rates were estimated by coalescing pregnancy rates of studies performed independently, and heterogeneity between the studies was investigated. The meta-analysis included 24 studies that determined pregnancy rates in 78 different groups consisting of 1934 sheep with five different synchronization protocols in Turkey between 2001 and 2020. Among the different synchronization methods, the P4+PMSG group (90.37%) during the breeding season and P4+PGF2 alpha (69.77%) and P4 (68.75%) groups during the non-breeding season showed the highest pregnancy rate. Also, the effect size of P4+PMSG application during the breeding season was calculated as 0.934 (95% confidence interval: 0.901-0.967), and the effect size of P4+PGF2 alpha application during the non-breeding season was calculated as 0.709 (95% confidence interval: 0.406-1.013). To conclude, the combination of P4+PMSG during the breeding season and progestogen and other hormone applications during the nonbreeding season are the most effective methods for estrus synchronization and for achieving the desired pregnancy rates.
Keywords: breeding season; estrus synchronization; ewes; meta-analysis; reproductive management